DEVELOPING PUPILS ENTHUSIASM TO ENGLISH LANGUAGE THROUGH THE ROLE PLAYING - Valiyeva Xilolaxon,; Igamberdieva Shahnoza, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The purpose of this article is to study the motivation of students to learn English using a role-playing game. Role-playing is an effective method of revitalizing teaching and increasing the interest of students in a foreign language who are learning this language in a very impressive way. This study focuses on how to successfully increase the level of students' conversational speech. To do this, teachers should choose a real and relevant topic, and vocabulary should depend on this topic. Teachers should create a comfortable atmosphere so that students do not get nervous and do not feel pressure.